Religion in Practice: Ecology, Education, Pluralism, and Vulnerability in Contemporary Contexts - Busro, Busro (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This issue presents interdisciplinary research that explores the intersection of religion with contemporary global and local challenges, including ecological sustainability, pluralism, and social vulnerability. The articles in this issue introduce significant contributions to religious studies by examining how religious practices can respond to environmental and social crises. Key contributions include the role of indigenous wisdom and ecological spirituality in environmental conservation, as well as the impact of religious pluralism in educational contexts that foster interfaith understanding and tolerance. Additionally, this issue discusses the importance of a pastoral approach emphasising relational accompaniment in pluralistic societies and the need to develop policies that are sensitive to social trauma. Through these approaches, this issue affirms that religious studies must be viewed as a source of ethical reflection and social transformation in addressing the complexities of the contemporary world. The primary focus of this issue is on integrating theological perspectives, ethics, and social action as a step towards building inclusive and just societies.